Pengaruh Modal Sosial pada Perilaku Berbagi Pengetahuan dan Kinerja: Studi Kasus di Pemasok Komponen Otomotif Astra Group - Sukoco, PhD, Badri Munir; Hardi, Hardi Hardi (SBM ITB, 2013)
As the biggest automotive group producer in Indonesia, Astra Group maintains relationship with its suppliers extensively, in which suppliers with small and medium enterprises (SMEs) for motorcycle reach 94% while automobile for about 60%. The existing relationships create strong social capital and offer positive consequences for both parties. Using social capital theory, this study empirically tests the effect of social capital on knowledge sharing between buyer (Astra Group) and supplier as well as suppliers' performance. Further, this study argues that perceived interdependency to the buyer could moderate the effect of social capital on suppliers' performance. Based on a survey among 211 suppliers' of Astra Group, the results indicate that social capital mainly influences suppliers' performance. The moderating effect of interdependency is not confirmed in this study. Consistent with the developed hypotheses, relational social capital is developed by cognitive and structural social capital. Managerial and academic implications are presented in this study.Keywords: social capital, knowledge sharing, suppliers' performance, interdependency, Astra Group